Enterobius vermicularis as a cause of acute appendicitis in a child with acute lymphocytic leukemia: A case report - Shalaleh Ganji; Iraj Mobedi; Azim Rezamand; Farshid Ardabili; Pooya Yari; Majid Khanmohammadi (Medical Laboratory Journal, 2025)
Background: Enterobius vermicularis is the most important intestinal parasite in children worldwide. When this parasite migrates unexpectedly, the larvae move out of the intestine and enter organs such as the appendix, and can cause health risks. Case presentation: An 8-year-old boy was admitted to the oncology clinic of Tabriz Children’s Hospital, complaining of fever of 39-40°C with abdominal pain, cramps, loss of appetite, weakness, and fatigue, associated with cervical lymphadenopathy, hepatomegaly, axillary mass, abdominal upper thigh, maculopapular rashes, and tiny petechiae on the chest and abdomen. Results: On CT examination of the chest, moderate mediastinal and mesenteric lymphadenopathy was noted. The patient was hospitalized with a definitive diagnosis of acute lymphoblastic leukemia. On the seventh day of hospitalization, the patient developed additive colic pain (Contraction and cramping) around the umbilicus and concomitantly developed pain downward and rightward into the abdomen. Based on the clinical findings, the patient was thought to have acute appendicitis. Pathological examinations showed that E. vermicularis was the cause of the appendicitis. Conclusion: The results of this study indicate that this parasite may be associated with inflammation of the appendix in patients with acute lymphoblastic leukemia. A screening program is still required in patients with immunodeficiency or those taking immunosuppressive drugs.